2008
DOI: 10.1093/brain/awn273
|View full text |Cite
|
Sign up to set email alerts
|

Hyperexcitability of parietal-motor functional connections in the intact left-hemisphere of patients with neglect

Abstract: Hemispatial neglect is common after unilateral brain damage, particularly to perisylvian structures in the right-hemisphere (RH). In this disabling syndrome, behaviour and awareness are biased away from the contralesional side of space towards the ipsilesional side. Theoretical accounts of this in terms of hemispheric rivalry have speculated that the intact left-hemisphere (LH) may become hyper-excitable after a RH lesion, due to release of inhibition from the damaged hemisphere. We tested this directly using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
156
3
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(179 citation statements)
references
References 35 publications
15
156
3
5
Order By: Relevance
“…Our observation of a reduction in visuospatial neglect after cTBS over the unaffected PPC is in line with other noninvasive brain stimulation studies, which used singlepulse TMS and paired TMS as a 'virtual lesion' technique, 23,24 low-frequency ( 1 Hz) repetitive TMS, 17,24,25 cathodal transcranial direct current stimulation 26 or continuous TBS. 10,12 Koch et al 10 applied left PPC TBS in two sessions per day with an interval of 15 min every day for 2 weeks (10 days), which reduced hemispatial neglect for up to 2 weeks after treatment: behavioural inattention test scores improved by 16.3% at There were no significant differences between the treatment groups (post hoc tests: least significant difference or Student-Newman-Keuls).…”
Section: Discussionsupporting
confidence: 90%
“…Our observation of a reduction in visuospatial neglect after cTBS over the unaffected PPC is in line with other noninvasive brain stimulation studies, which used singlepulse TMS and paired TMS as a 'virtual lesion' technique, 23,24 low-frequency ( 1 Hz) repetitive TMS, 17,24,25 cathodal transcranial direct current stimulation 26 or continuous TBS. 10,12 Koch et al 10 applied left PPC TBS in two sessions per day with an interval of 15 min every day for 2 weeks (10 days), which reduced hemispatial neglect for up to 2 weeks after treatment: behavioural inattention test scores improved by 16.3% at There were no significant differences between the treatment groups (post hoc tests: least significant difference or Student-Newman-Keuls).…”
Section: Discussionsupporting
confidence: 90%
“…In the Shindo et al (2006) study, six sessions of rTMS improved the performance of two right brain-damaged patients on several subtests of the Behavioral Inattention Test (BIT) up to 6 weeks after treatment. After a single low-frequency rTMS session, Koch et al (2008) observed an improvement in the naming of visual chimeric figures in 12 right brain-damaged patients and in the Song et al (2009) trial, two sessions of rTMS per day during 14 days ameliorated line bisection and line cancelation for up to 14 days after treatment in 7 patients with right brain damage. Lim et al (2010) gave 1 Hz trains of 900 pulses for 5 days per week during 2 weeks to seven patients with right brain damage.…”
Section: Non-invasive Brain Stimulationmentioning
confidence: 92%
“…Other studies with small right brain lesioned patient groups and no control condition, using low-frequency rTMS inhibiting the left parietal cortex are those of Shindo et al (2006), Koch et al (2008), Song et al (2009), andLim et al (2010). In the Shindo et al (2006) study, six sessions of rTMS improved the performance of two right brain-damaged patients on several subtests of the Behavioral Inattention Test (BIT) up to 6 weeks after treatment.…”
Section: Non-invasive Brain Stimulationmentioning
confidence: 99%
“…38 The unaffected hemisphere may become hyperexcitable (increased motor evoked potential amplitude at a given test stimulus intensity), possibly due to lack of inhibition from the damaged hemisphere. 71,114 In injury settings, low-frequency TMS has been be applied to decrease hyperexcitability in the contralesional motor cortex, 44,91 and high-frequency TMS has been applied to increase the excitability of ipsilesional motor cortex 64 or dorsolateral prefrontal cortex (DLPFC). 84 Using these different responses to changing frequencies, TMS near the time of motor training of the affected hand after stroke was determined to enhance hand function.…”
Section: Noninvasive Stimulation For Motor Deficitsmentioning
confidence: 99%
“…Among patients with unilateral stroke, TMS of the unaffected parietal cortex reduced symptoms of contralesional visuospatial neglect. 71,81,131 In a pilot study of 2 patients with right hemispheric infarction who had unilateral spatial neglect, 2 weeks of TMS to the unaffected parietal cortex led to significant improvements in skills relevant to visual neglect. 131 In addition, TMS may also be effective in improving recovery from poststroke aphasias.…”
Section: Noninvasive Stimulation For Posttraumatic Cognitive Sequelaementioning
confidence: 99%